2020
DOI: 10.1186/s12888-020-2453-4
|View full text |Cite
|
Sign up to set email alerts
|

STUDY PROTOCOL: EXPOSURE IN VIRTUAL REALITY FOR SOCIAL ANXIETY DISORDER - a randomized controlled superiority trial comparing cognitive behavioral therapy with virtual reality based exposure to cognitive behavioral therapy with in vivo exposure

Abstract: Background: Social Anxiety Disorder (SAD) is characterized by an intense fear of negative judgement by others. Cognitive Behavioral Therapy (CBT) is recommended for treatment, but a substantial part of individuals with SAD either do not seek treatment or drop-out. CBT with Virtual Reality (VR)-based exposure has several advantages compared to traditional exposure methods, mainly due to increased control of situational elements. The aim of the current study is to develop a CBT program containing VR-based exposu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 61 publications
1
6
0
1
Order By: Relevance
“…Safir et al ( 45 ) showed that after 1 year of clinical improvement, the reduction of social phobia symptoms is still maintained, regardless of whether the therapy was performed with VRET or in vivo exposure ( 42 ). Similar in other studies that conducted long-term follow-up of patients after treatment, it was possible to demonstrate the durability of the treatment effect after the completion of VRET ( 46 , 47 , 49 , 51 ). This may indicate no need for maintenance therapy with VR.…”
Section: Discussionsupporting
confidence: 70%
“…Safir et al ( 45 ) showed that after 1 year of clinical improvement, the reduction of social phobia symptoms is still maintained, regardless of whether the therapy was performed with VRET or in vivo exposure ( 42 ). Similar in other studies that conducted long-term follow-up of patients after treatment, it was possible to demonstrate the durability of the treatment effect after the completion of VRET ( 46 , 47 , 49 , 51 ). This may indicate no need for maintenance therapy with VR.…”
Section: Discussionsupporting
confidence: 70%
“…Focusing on the workplace challenges experienced by healthcare workers is important, as there is consensus across much of the literature that pandemic preparedness in workplaces can alleviate mental health stress experienced by workers [ 39 , 45 ], as does having a supportive workplace [ 46 ]. Overall, participants in this study argued that health systems were unprepared for the pandemic and that there was limited support provided to frontline health workers.…”
Section: Discussionmentioning
confidence: 99%
“…Clearly, there is no point conducting studies on reducing anxiety in a VR environment which candidates do not find realistic and so do not react in a way comparable way to a real environment (Clemmensen et al, 2020). However, both the quantitative and qualitative results of the research confirmed that the candidates had similar reactions in both presentation experiences, and it can therefore be inferred that they found the VR experience to be quite realistic.…”
Section: Discussion and Suggestionsmentioning
confidence: 87%